The clinical characteristics and gene mutations associated with thyroid hormone resistance syndrome coexisting with pituitary tumors - Zhao, Junyu; Xu, Lusi; Li, Chunyu; Wang, Fei; Liao, Lin; Dong, Jianjun (Frontiers in Endocrinology, 2023)
Aims: Both resistance to thyroid hormone (RTH) and pituitary tumours are rare diseases and the differential diagnosis of these two diseases is difficult in some cases. There are also patients who have both conditions, making diagnosis more difficult. To better understand this aspect, we analysed the clinical characteristics and gene mutations of RTH coexisting with pituitary tumours. Methods: Database retrieval was conducted in the following databases: PubMed, Cochrane Library, and SinoMed, and the search contents werecase reports or case series of patients with RTH coexisting with pituitary tumours. The demographic, clinical manifestations and imaging characteristics of pituitary tumours and gene mutations were summarized. Results: Thirteen articles involving 16 patients with RTH coexistent with pituitary tumours, including 13 females, 1 male and two patients with unknown sex, were included. The patients ranged from 10 to 79 years old and most patients were 41-55 years old (43.75%). The 16 patients were from 7 different countries and 3 continents (Asia, Americas, and Europe). All the patients showed an abnormal secretion of TSH, and five patients underwent transsphenoidal surgery. Finally, four patients were pathologically confirmed to have TSHoma. A total of eleven different mutations occurred at nine amino acid sequence sites (251, 310, 344, 347, 383, 429, 435, 438 and 453). Two different mutations occurred in both the No. 435 and No. 453 amino acid sequences. Fourteen patients provided their treatment histories, and all had undergone different treatment regimens. Conclusions: Patients with both RTH and pituitary tumours had multiple clinical manifestations and different thyroid functions, imaging characteristics of pituitary tumours, genetic mutations of THRβ and treatments. However, due to the limited number of cases, patients were mainly female. Further studies with more cases that focus on the mechanism are still needed.